Constitutive visions : indigeneity and commonplaces of national identity in republican Ecuador - Olson, Christa J., 1978- (Rhetoric and democratic deliberation., 2014)
"Examines the history of national identity in Ecuador from 1857 to 1946. Brings together recent work in rhetoric, visual culture, transnationalism, and Latin American studies to explore the different visions of indigenous people that circulated in speeches, periodicals, and art"--Provided by publisher